The Interpretation of Patterns and Symmetry in the Qur'an: Does Mathematics Serve as Proof of Divinity or Merely an Aesthetic Interpretation? - Nurhikmah, Nurhikmah; Al Ayyubi, Ibnu Imam; Masfuroh, Ai Sri; Noerzanah, Firda; Rahmawati, Siti (Borneo International Journal of Islamic Studies, 2025)
This study aims to explore the meaning of patterns and symmetry in the Qur’an and the role of mathematics in the context of divinity and aesthetics. Using a qualitative approach with a phenomenological study design, this research involves scholars of Qur’anic interpretation, religious educators, and mathematicians who understand the relationship between mathematics and religion. A total of nine participants were selected through purposive sampling based on specific criteria: (1) academic or professional background in Qur’anic exegesis, religious education, or mathematics, (2) engagement in interdisciplinary discourse between science and religion, and (3) willingness to participate in in-depth interviews. Data were collected through in-depth interviews and textual analysis of the Qur’an using an interpretative approach. The findings indicate that patterns and symmetry in the Qur’an serve as aesthetic elements and representations of the order in God’s creation. Most participants perceive this order as evidence of God’s power in creating the universe with mathematical laws humans can comprehend. However, some perspectives view patterns and symmetry primarily as aesthetic interpretations that enrich the spiritual experience of Muslims. Overall, this study opens opportunities for integrating the understanding of patterns and symmetry in the Qur’an with mathematics education, allowing science and religion to be comprehended as a harmonious unity.